2020
DOI: 10.1101/2020.11.24.20238261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Kids Are Not Alright: A Preliminary Report of Post-COVID Syndrome in University Students

Abstract: BackgroundPost-COVID syndrome is increasingly recognized by the medical community but has not been studied exclusively in young adults. This preliminary report investigates the prevalence and features of protracted symptoms in non-hospitalized university students who experienced mild-to-moderate acute illness.Methods148 students completed an online study to earn research credit for class. Data from COVID-19 positive participants with symptoms ≥28 days (N=22) were compared to those who fully recovered (N=21) an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
1
39
0
1
Order By: Relevance
“…In a study of 180 participants (8 of whom had been hospitalized) interviewed during the acute phase of disease and at follow-up phone calls, persistent symptoms were reported by 53% of symptomatic participants at a mean follow-up time of 125 days (most often fatigue, loss of smell and taste, and arthralgias) [31]. Larger survey-based studies on COVID-19-related symptoms in a multitude of participants with self-reported COVID-19 are available online, although not yet peer-reviewed (Table 4 presents an overview of studies) [32,33,34,35,36,37]. Characteristic for most of these studies is the acceptance of self-reported COVID-19 status by participants without laboratory confirmation of COVID-19-status, and recruitment of participants with the specific aim of COVID-19 symptom reporting likely inferred a substantial selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 180 participants (8 of whom had been hospitalized) interviewed during the acute phase of disease and at follow-up phone calls, persistent symptoms were reported by 53% of symptomatic participants at a mean follow-up time of 125 days (most often fatigue, loss of smell and taste, and arthralgias) [31]. Larger survey-based studies on COVID-19-related symptoms in a multitude of participants with self-reported COVID-19 are available online, although not yet peer-reviewed (Table 4 presents an overview of studies) [32,33,34,35,36,37]. Characteristic for most of these studies is the acceptance of self-reported COVID-19 status by participants without laboratory confirmation of COVID-19-status, and recruitment of participants with the specific aim of COVID-19 symptom reporting likely inferred a substantial selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Walsh-Messinger et al . study found patients with post-COVID-19 syndrome had higher ratings of depression subscale markers of altered sleep and thinking, but depression severity was not significantly different with patients not diagnosed with COVID-19 (Walsh-Messinger et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…In one of the post-SARS-Cov-2 infection studies in young patients, 92% were found to have ongoing cardiorespiratory symptoms with organ dysfunction representing comprised of: 32% impairment of the heart, 33% impairment of lungs, and 12% impairment of the kidneys (Dennis et al, 2020). In another post-COVID-19 syndrome study, 96% of the patients were female and experienced statistically significant exercise intolerance, dyspnea, and chest pain when compared to those not diagnosed with COVID-19 (Walsh-Messinger et al, 2020). Moreover, Walsh-Messinger et al .…”
Section: Discussionmentioning
confidence: 96%
“…Most studies refer to their patient recruitment in terms of recovery (e.g., "COVID-19 survivors" 56 or "discharged COVID-19 patients" 57 ) or clinical course (e.g., "medium-and long-term consequences" 58 or "delayed return to usual health" 59 ). A number of studies did refer to their participant groups using terms like "Long COVID", 13,[60][61][62][63][64][65][66][67][68] "post-acute COVID-19", 69,70 "post-COVID syndrome", 71 or "post-acute COVID-19 syndrome", 72 but these terms were not standardized among studies. A few studies 46,60 acknowledged the proposed distinction at 12 weeks post-infection between post-acute COVID-19 and chronic COVID-19, 37 but otherwise the definitions used typically did not refer to any proposed operationalizations of Long COVID.…”
Section: Literature Reviewmentioning
confidence: 99%